(untitled) (Bhartiya Knowledge Systems, 2024)
The Indian Knowledge System (IKS) embodies an extensive repository of multidisciplinary knowledge, spanning philosophy, science, art, medicine, and spirituality, developed over millennia. This research delves into the essence of IKS, emphasizing its historical progression, unique features, and applicability in contemporary societal and educational contexts. Utilizing a blend of historical analysis and contemporary evaluation, the paper illustrates the resilience and relevance of IKS in modern frameworks, such as the National Education Policy 2020. By bridging the gap between traditional wisdom and modern innovations, this study showcases how IKS can address current global challenges, including sustainability and holistic education.